2020
DOI: 10.1016/j.jamcollsurg.2019.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Time Is Money: Can Punctuality Decrease Operating Room Cost?

Abstract: BACKGROUND: Inefficient operating room (OR) use wastes resources. Studies have suggested "first case on-time starts" (FCOTS) reduce OR "idle time," yet no direct association between FCOTS and markers of OR efficiency, like "last case on-time end" (LCOTE) or overtime costs, have been reported. We performed this study to evaluate factors associated with FCOTS, LCOTE, and OR overtime costs. STUDY DESIGN: In April 2017, our medical center launched an FCOTS improvement initiative. Prospectively collected data conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 10 publications
(12 reference statements)
0
11
0
Order By: Relevance
“…Although we could not directly measure real overtime costs, many studies have shown that faster OR turnover can reduce OR costs. 20 Urinary retention, the most common complication in the GB group (w10%), was significantly less frequent in the FH group (w1%), likely because FH TPB mostly omits the adenoma region but emphasizes obtaining high-quality cores around the peripheral and anterior/fibromuscular zones.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although we could not directly measure real overtime costs, many studies have shown that faster OR turnover can reduce OR costs. 20 Urinary retention, the most common complication in the GB group (w10%), was significantly less frequent in the FH group (w1%), likely because FH TPB mostly omits the adenoma region but emphasizes obtaining high-quality cores around the peripheral and anterior/fibromuscular zones.…”
Section: Discussionmentioning
confidence: 94%
“…Although we could not directly measure real overtime costs, many studies have shown that faster OR turnover can reduce OR costs. 20…”
Section: Discussionmentioning
confidence: 99%
“…Even though there are multiple studies in the literature examining the inefficiencies of the operative and turn-over phases [2,6,[10][11][12][13][14][15][16][17], few studies have assessed inefficiencies related to the preparatory phase. Caggiano et al [18] found that preparatory time's variability is high, up to 30 min per case, even though they excluded cases that required special positioning and special equipment, implying that the variability is not affected as much by the procedure type but rather by the workflow and preparation process [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, failures of RA, delays in the induction of anesthesia [26], and its unpredictable success rate [21,27] can lead to disorganization of the OR schedule. This may disrupt OR staf scheduling and increase costs [28][29][30].…”
Section: Introductionmentioning
confidence: 99%